Diseño de un plan de marketing para la empresa de productos lácteos “SIMPORLAC” de la ciudad de Otavalo, con el fin de lograr la mejor estrategia comercial y canales de distribución. - Cevallos, Evelyn G. (2022)
The research on the topic "DESIGN OF A MARKETING PLAN FOR THE DAIRY PRODUCTS COMPANY "SIMPORLAC" OF THE CITY OF OTAVALO, IN ORDER TO ACHIEVE THE BEST COMMERCIAL STRATEGY AND DISTRIBUTION CHANNELS" was developed in the city of Otavalo being the general objective to design a marketing plan to improve the commercial strategy and distribution channels of the company "SIMPORLAC" since the marketing plan allows to implement actions that lead to the desired result. This work consists of four chapters in which different topics were studied according to the importance of the research. Chapter one contains an introduction where the theoretical bases that will allow identifying and establishing the marketing and market repositioning strategies to be implemented are detailed. Chapter two will analyze the situational state of the company where the diagnostic matrix and the SWOT matrix will be elaborated. Chapter three will elaborate a market research study in the city of Otavalo, through a survey in order to contribute to the development of strategies for the implementation and success of the Marketing Plan. Chapter four consists of the development and design of a marketing plan to establish a better product commercialization strategy. The respective conclusions and recommendations to the company were determined, which will allow it to improve its performance and customer recognition.